The Critical Mediator Role of Process Management for Effective Industry 4.0 Implementation in SMEs - Kahveci, Eyup; Akgul, Arzu Karaman; Daim, Tugrul; Meissner, Dirk (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
This article investigates the pivotal role of Industry 4.0 (I4.0) process management (PM) in leveraging human resources (HR) and operational processes to align with strategic objectives and organizational structures, ultimately achieving competitive advantage. This article targeted small- and medium-sized enterprises (SMEs) in the manufacturing and service sectors in Istanbul, Turkey. Using a simple random sampling technique, we invited 475 firms to participate in a survey, yielding 207 usable responses. The data analysis was conducted in three stages: descriptive statistical analysis to illustrate the characteristics of the participating companies and respondents; confirmatory factor analysis to test the measurement models and ensure they fit the data; and causal analysis to evaluate the hypothesized relationships among the study's constructs. The findings reveal that PM serves as a critical mediator role in the successful implementation of I4.0. Specifically, the article identifies three primary goals in the I4.0 adoption process: strategic improvement, competitiveness, and organizational fit. Effective PM impacts these objectives through two major areas: HR and operations. This article highlights how I4.0 PM can act as a catalyst in the digital transformation of SMEs, ensuring that HR and operations are effectively harnessed to drive strategic change and organizational adaptation, and enhanced competitiveness.
Keywords: Fourth Industrial Revolution; Biological system modeling; Companies; Surveys; Europe; Costs; Catalysts; Internet of Things; Indexes; Context modeling; Digital transformation; Industry 4.0 (I4.0); process management (PM); small and medium-sized enterprises (SMEs); MODEL; Business & Economics; Engineering